PENGARUH KUALITAS PELAYANAN, PROMOSI, HARGA, KUALITAS PRODUK DAN CITA RASA TERHADAP KEPUASAN PELANGGAN PADA AYAM GEPREK WARUNG ENDUS SIBUAYA - Arinal Husna; Zuriani Zuriani; Sumitro Sumitro (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
This study aims to determine the effect of service quality, promotion, price, product quality and taste on customer satisfaction at Geprek chicken at Endus Sibuaya stall. The population in this study are consumers who buy directly at Ayam Geprek Warung Endus Sibuaya. In this study, using a sample of 84 people. This study used the simple random sampling method, where the penarika was randomized by providing equal opportunities for each member of the population to express their opinion. In simultaneous testing (Test F), it is known that service quality, promotion, price, product quality and taste have a positive and significant effect on customer satisfaction. Partially (t test) it is known that service quality and promotion have a positive and significant effect on customer satisfaction, while price, product quality and taste have no positive and significant effect on customer satisfaction. Meanwhile, targetting and market positioning do not have a positive and significant effect on competitive advantage. Through the determinant coefficient test, the Adjusted R Square value is 0.229 or 22.9. Customer satisfaction can be explained by service quality, promotion, price, product quality and taste while 77.1 can be explained by other variables which are not discussed in this study. Testing the feasibility of the research instrument and descriptive analysis of the characteristics of the respondents used SPSS (Statistical Package For The Social Science) software.